An Assessment of Usage of Power Point Presentation in Undergraduate Courses in Electrical & Electronics Engineering - Kittur, Javeed (Journal of Engineering Education Transformations, 2018)
Despite the need of the hour, many instructors are reluctant in introducing technology in classroom. The reasons for being reluctant could be lack of confidence, availability of time and lack of skills required for using technology. Power point presentations form the introductory step in incorporating technology in classroom. Power point presentation provides instructors an opportunity to build innovative and dynamic presentations that command students' attention and are fun to use. The cost incurred in preparing a presentation is economically and financially minimal. The advantages of using a power point presentation are; it provides visual appeal, animated graphics, notes in an organized manner, updated information in the slides using the web links, more of the class time can be used for executing activities and interacting with students. This study investigates students' perception on usage of power point presentation in class in comparison with chalk and talk. This activity was implemented in two courses Basic Electrical Engineering and Modern Control Systems.